Development and characterization of nanoemulsion as carrier for the enhancement of bioavailability of artemether. (October 2015) - Laxmi, Moksha; Bhardwaj, Ankur; Mehta, Shuchi; Mehta, Abhinav
Abstract The present study aimed to develop a kinetically stable nanoemulsion of artemether with improved solubility, stability and oral bioavailability. Nanoemulsion was prepared by ultrasonication technique using internal oil phase (consisted of the drug dissolved in coconut oil and span 80) and external phase (comprising tween 80 and ethanol dissolved in water). The formulations were optimized using various parameters like percentage transmittance, refractive index, drug content, viscosity, zeta potential and release rate. Stability studies were conducted for a period of 90 days using stability chambers. In vivo studies of the developed formulations were conducted on Wistar rats and data were analyzed statistically. The nanoemulsion as observed under transmission electron microscope were found to be spherical in shape with an average size of 79.0 nm and a zeta potential of −15 mV which indicated of good electrokinetic stability of nanoemulsion . Nanoemulsion was found to be clear and transparent in appearance with a percentage transmittance of 98.2. Refractive index of 1.32 of the nanoemulsion indicated the isotropic nature of the drug. Release rate of the drug from the nanoemulsion formulation was found to be quite significant (P < 0.001) as compared to the plain drug. In vivo oral bioavailability of the nanoemulsion formulation was found to be 2.6-fold higher than the plain drug (˜ 40%) as observed from pharmacokinetic studies. Thus it was observed that nanoemulsion proved itself as a promising alternate for improving the bioavailability of artemether.